12.9k views
0 votes
Simplify
i^(11)

1 Answer

5 votes

Answer:

The simplified given expression is
i^(11)=-i

Explanation:

Given expression is
i^(11)

To simplify the given expression
i^(11) as below:


i^(11)=i^(10+1)


=i^(10).i^1 ( using the property
a^(m+n)=a^(m).a^(n) )


=(i^2)^5.i ( using the property
(a^m)^n=a^(mn) )


=(-1)^5.i ( since
i^2=-1 )


=(-1).i ( since power is odd so we get -1 )


=-i

Therefore
i^(11)=-i

Therefore the simplified given expression is
i^(11)=-i

User Raman Mishra
by
5.3k points